2010
DOI: 10.1890/10-0479.1
|View full text |Cite
|
Sign up to set email alerts
|

Active density‐dependent habitat selection in a controlled population of small mammals

Abstract: Abstract. Density-dependent habitat selection has numerous and far-reaching implications to population dynamics and evolutionary processes. Although several studies suggest that organisms choose and occupy high-quality habitats over poorer ones, definitive experiments demonstrating active selection, by the same individuals at the appropriate population scale, are lacking. We conducted a reciprocal food supplementation experiment to assess whether voles would first occupy a habitat receiving extra food, then ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…The absence of posttreatment crowding in this study suggests that subordinate males could not force territorial individuals to share resources, or that they found alternative territories elsewhere in the study area. Territory size was negatively correlated with food abundance (see also Stenger 1958, Smith andShugart 1987) and postharvest adjustments in territory size by males banded in the preharvest year indicate a high degree of behavioral plasticity and adaptive habitat selection (see also Haugen et al 2006, Morris and MacEachern 2010, Chalfoun and Schmidt 2012. The observed pattern is also consistent with food-value theory (Stenger 1958, Marshall andCooper 2004), which predicts that males from treated plots would increase the size of their territory to compensate for the postharvest decline in food abundance.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The absence of posttreatment crowding in this study suggests that subordinate males could not force territorial individuals to share resources, or that they found alternative territories elsewhere in the study area. Territory size was negatively correlated with food abundance (see also Stenger 1958, Smith andShugart 1987) and postharvest adjustments in territory size by males banded in the preharvest year indicate a high degree of behavioral plasticity and adaptive habitat selection (see also Haugen et al 2006, Morris and MacEachern 2010, Chalfoun and Schmidt 2012. The observed pattern is also consistent with food-value theory (Stenger 1958, Marshall andCooper 2004), which predicts that males from treated plots would increase the size of their territory to compensate for the postharvest decline in food abundance.…”
Section: Resultssupporting
confidence: 61%
“…Indeed, the IDD tends to receive more support than the IFD (reviewed by Rodenhouse et al 1997, Piper 2011). Yet, there is a growing body of evidence suggesting that the IFD can indeed apply to birds (Weidinger 2000, Sebastian-Gonzalez et al 2010, Quaintenne et al 2011 and many other taxa (Beckmann and Berger 2003, Rieger et al 2004, Haugen et al 2006, Morris and MacEachern 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since meadow voles responded positively to CWD at the stand-scale, the lack of associations at the fine-scale that we observed may have been caused by several factors. An overriding regulatory factor (Krohne and Burgin, 1990), the lack of predation as well as other density-dependent factors such as intraspecific competition (Turner and Iverson, 1973;Oatway and Morris, 2007;Morris and MacEachern, 2010) may have had a significant impact on the local distribution of meadow voles.…”
Section: The Effects Of Scale On Microhabitat Associationsmentioning
confidence: 99%
“…Two related studies (Oatway and Morris, 2007;Morris and MacEachern, 2010) observed a strong spatial structure in enclosures at the scale of 50 m with meadow voles. Whereas Bowman et al (2001) found a similar pattern (from spatial autocorrelation analyses) for southern red-backed voles at the scale of 125 m in open forests, the pattern became weak at distances of more than 533 m. These distances match daily movements of voles and mice inside their home range (Tallmon and Mills, 1994;Ribble et al, 2002;Thompson et al, 2009).…”
Section: Introductionmentioning
confidence: 95%